The chemoenzymatic synthesis of glycan-terminated oligo(Leu)x - Black, Sarah P.; Liu, Melinda; Castillo, Cesar; Coradeli, Wynne; Totsingan, Filbert; Edson, Cody B.; Khare, Sagar D.; Gross, Richard A. (Frontiers in Catalysis, 2024)
Glycopeptides contain carbohydrate moieties (glycans) covalently attached to the side chain and/or terminal peptide units. Since glycans are present on cell surfaces, these constructs can potentially address a wide array of therapeutic functions. To overcome the deficiencies associated with current synthetic routes to glycopeptides, such as costly processes and toxic reagents, this work aimed to develop versatile environmentally friendly protease-catalyzed peptide synthetic (PCPS) routes to peptides decorated with a glycan at their N-terminus. 'Grafters' were first synthesized that consist of a glycan conjugated directly, or through a spacer, to the amine group of L-Phe-ethyl ester (Phe-OEt). The role of Phe-OEt is to increase the conjugate's recognition by the protease (papain) catalytic active site. A series of grafters were synthesized with variation of the glycan structure, linkage-chemistry, and presence of an oligo(ethylene glycol) 'spacer' of varied length between the glycan and Phe-OEt moiety. High grafter efficiency will result by the successful acceptance of the grafter at the enzymes S1/S2 subsites, formation of an acyl-enzyme complex and subsequent conversion to glycan-terminated-oligo(Leu)x (x ≥ 1), as opposed to construction of non-glycan Nterminated oligo(Leu)x. While glycan-Phe-OEt grafters without a spacer between the glycan and Phe-OEt resulted in low grafter efficiency (8.3 ± 2.0%), insertion of a short oligo(ethylene glycol) spacer between the glycan and Phe-OEt moieties (glycan-PEGn-Phe-OEt, n ≥ 3) increased the grafter efficiency by 3-fold to 24.5 ± 1.8%. In addition, computational modeling was performed using Rosetta software provided insights on a molecular level of how grafter efficiency is influenced by the PEG spacer length.